The phase error reduction using window functions in digital holography - Yan, Facai (2018)
Digital holography (DH) is a 3D imaging technique with a theoretical axial accuracy of better than 1-2 nanome-ters. However, practically, the axial error has been quoted to be tens of nanometers which is much larger than the theoretical value. Previous studies of the axial error mainly focused on the phase error introduced by lens. However, it is found that CCD aperture size is also an important contributors to axial error by our group. It is necessary to investigate the reduction approach of such axial error. The most possible connection between the limited CCD aperture size and the axial error is the diffraction effect. Window functions once have been applied to digital holograms for diffraction suppression and improve the lateral resolution of the intensity image. How-ever, their impacts on phase image and the associated axial dimension measurement are still unknown. In this paper, window functions are applied to digital holograms for phase/axial error reduction. Both simulation and experiment are performed. Moreover, the relation between axial error and window functions is also illustrated by the mathematical formulas derived in the theory. And all the results validate that the window functions can reduce the axial error of digital holography.